2021
DOI: 10.1186/s12912-021-00711-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, student nurses’ knowledge and practices of needle stick injuries during clinical training: a cross-sectional survey

Abstract: Background The incidence of needle stick injuries is higher among nurses with a low level of knowledge on the prevention of needle stick injury, and who have not received the relevant training during their undergraduate study. The aim of this study was to determine the level of knowledge of the prevention guidelines and the prevalence of needle stick injury among students in Oman. Methods An online cross-sectional survey using a questionnaire and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…The researchers prepared the questionnaire based on NSI studies ( 6 , 8 ). The questionnaire had four parts.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers prepared the questionnaire based on NSI studies ( 6 , 8 ). The questionnaire had four parts.…”
Section: Methodsmentioning
confidence: 99%
“…Attia et al (19) found that one of the reasons for occupational hazard exposure is the lack of occupational health and safety education. One of the most common hazards encountered by nursing students is needle-stick injuries, frequently caused by the recapping of needles after use (20,21). Suliman et al (22) stated that 46.2% of nursing students do not know that they should not recap the needle after use.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Eyi et al (1), carelessness also played a major role in occupational accidents. Al Qadire et al (20) found that one of the major causes of needle-stick injuries was talking to others. Nursing students, in this study, stated that they experienced occupational hazard exposure due to the…”
Section: Discussionmentioning
confidence: 99%
“…For instance, not using the correct recapping technique increases the risk of needle stick injuries. Al Qadire et al [22] showed that the knowledge score of dental students regarding the needle stick injuries and how to prevent them was 6 out of 10. They reported the occurrence of needle stick injuries during preparation for anesthesia administration in 70% of those who experienced such injuries.…”
Section: Discussionmentioning
confidence: 99%